Transformasi Digital Layanan Sertipikat Tanah Elektronik di Kantor Pertanahan Kabupaten Tulungagung - Mirtha Ilmi; Eva Hany Fanida; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Digital transformation in public services represents a strategic shift in integrating information technology into governmental administrative systems to enhance service efficiency, transparency, and accountability. One prominent innovation in this effort is the adoption of electronic land certificates initiated by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) as part of land service modernization. This policy is formally regulated under Ministerial Regulation No. 3 of 2023 concerning electronic documents in land registration. This study employs a descriptive qualitative approach to examine the implementation process, identify enabling and constraining factors, and assess the impact of electronic land certificates on the quality of land services. Data were obtained through interviews, field observations, and document analysis at the Tulungagung Regency Land Office and analyzed using the interactive model proposed by Miles and Huberman. The findings indicate that electronic land certificates contribute significantly to improving service efficiency, administrative speed, and data security. Nonetheless, several challenges persist, including inadequate network infrastructure in rural areas, limited public digital literacy, and insufficient information technology personnel. Despite these constraints, the initiative has been positively received and reflects the local government’s commitment to advancing digital governance and good governance principles. The effectiveness of this transformation largely depends on institutional readiness, technological support, and community engagement.